Performance of Chlorella sp. and Multicultural Bacteria in Removing Pollutants from Nutrient-Rich Wastewater - Mohd Edyazuan; Atiqah Zainal Abidin; Roslan Noorain; Sharifah Mariam Syed Hitam; Lusi Ernawati; Rosnah Abdullah; Ahmad Shoiful; Rozyanti Mohamad (ASEAN Journal of Chemical Engineering, 2022)
The most common method of treating palm oil mill effluent (POME) is by using various types of bacteria communities. However, the utilization of microalgae in consuming the high nutrient content in wastewater offer additional benefit, particularly for CO2 sequestration. In this study, we proposed to evaluate the performance of multicultural bacteria obtained from municipal wastewater and Chlorella sp. for batch treatment of POME at different COD concentrations (ranges between 600 to 1,300 mg/L), microalgae species (C. vulgaris and C. pyrenoidosa) and speed of agitation (0 and 150 rpm). The results showed that between the bacteria and microalgae that are involved in POME treatment, microalgae give high removal of colour (93%) and ammoniacal nitrogen (95%). As for the COD and phosphate removal, both microorganisms show comparable performances. It was observed that C. pyrenoidosa was able to remove more colour compared to C. vulgaris where higher lipid yield production was obtained (47.6%). However, there is no significant impact of agitation on pollutant removal. This study also reveals that co-cultivation of different microalgae species does not affect the efficiency of the system. This study provides an important insight into developing an efficient and environmentally friendly method to treat wastewater by incorporating green technology in the treatment system